2018
DOI: 10.1111/jre.12631
|View full text |Cite
|
Sign up to set email alerts
|

Gingival fibroblasts prevent BMP‐mediated osteoblastic differentiation

Abstract: Objectives The inhibitory action of the superficial gingival connective tissues may limit the regenerative potential of alveolar bone in periodontal therapy or dental implant applications. The aims of this study were to investigate the hypothesis that gingival fibroblasts (GF) can inhibit bone morphogenetic protein (BMP)‐induced osteoblastic differentiation, to determine their expression of BMP inhibitors, and finally to determine whether reduction of these inhibitors can relieve suppression of os… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 39 publications
2
15
0
Order By: Relevance
“…Inhibition or induction of GREM‐1 changed the osteogenic differentiation of PDLSCs under inflammatory conditions (Figure 7). Similar results have been reported by Ghuman, showing that GREM‐1 can also limit coronal alveolar bone regenerative potential during oral and periodontal surgery by inhibiting BMP‐induced bone formation 61 . Other studies have shown that GREM‐1 plays an important regularly role in organogenesis of the limbs and kidneys, 62 and mutations in GREM‐1 lead to abnormalities of the limbs, lungs, and kidneys in mice 63 …”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Inhibition or induction of GREM‐1 changed the osteogenic differentiation of PDLSCs under inflammatory conditions (Figure 7). Similar results have been reported by Ghuman, showing that GREM‐1 can also limit coronal alveolar bone regenerative potential during oral and periodontal surgery by inhibiting BMP‐induced bone formation 61 . Other studies have shown that GREM‐1 plays an important regularly role in organogenesis of the limbs and kidneys, 62 and mutations in GREM‐1 lead to abnormalities of the limbs, lungs, and kidneys in mice 63 …”
Section: Discussionsupporting
confidence: 77%
“…Similar results have been reported by Ghuman, showing that GREM-1 can also limit coronal alveolar bone regenerative potential during oral and periodontal surgery by inhibiting BMP-induced bone formation. 61 Other studies have shown that GREM-1 plays an important regularly role in organogenesis of the limbs and kidneys, 62 and mutations in GREM-1 lead to abnormalities of the limbs, lungs, and kidneys in mice. 63 Taken together, these results show that P2X7R has not been identified, and more in vivo experiments are needed to verify the positive influence of P2X7R on tissue regeneration.…”
Section: The Lipid Bilayers Of Exosomes Can Effectively Protect Multiplementioning
confidence: 99%
“…We further measured the expression levels of important factors involved in the regulation of osteoblastic differentiation, such as BMP-2 [ 20 ], Ocn [ 21 ], and ALP [ 22 ]. We found that BMP-2, Ocn, and ALP ( Figure 3a-b ) were significantly upregulated in osteogenic medium-cultured MC3T3‑E1 cells at both the mRNA and protein levels, and pronouncedly further upregulated by 20 μM Omarigliptin, revealing the regulatory function of Omarigliptin on osteoblastic differentiation is associated with these factors.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, SFRP1 expression was higher in hDPCs than in hPDLCs and hGFs. SFRP1 expression was confirmed in cultured rat gingival fibroblasts [ 25 ]. Other previous studies demonstrated that bone-lining osteoblast-like stromal cells and osteoclasts express SFRP1 [ 26 ] and that SFRP1 is expressed much more strongly in the periodontal ligament than in alveolar bone and cementum [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Various signals, such as growth factors, chemokines, and extracellular matrices, are involved in the regeneration and homeostasis of the dentin-pulp complex [ 25 , 26 , 27 , 28 , 29 , 30 ]. Additionally, the mesenchymal stem/progenitor cell population in pulp is considered to differentiate into odontoblast-like cells, which generate reparative dentin in response to injury [ 10 , 31 ].…”
Section: Discussionmentioning
confidence: 99%